Dicer-Dependent Biogenesis of Small RNAs and Evidence for MicroRNA-Like RNAs in the Penicillin Producing Fungus Penicillium chrysogenum. - Tim A Dahlmann; Ulrich Kück (PLoS ONE, 2015)
MicroRNAs (miRNAs) are non-coding small RNAs (sRNAs) that regulate gene expression in a wide range of eukaryotes. In this study, we analyzed regulatory sRNAs in Penicillium chrysogenum, the industrial producer of the β-lactam antibiotic penicillin. To identify sRNAs and microRNA-like RNAs (milRNAs) on a global approach, two sRNA sequencing libraries were constructed. One library was created with pooled total RNA, obtained from twelve differently grown cultures (RNA Mix), and the other with total RNA from a single submerged cultivation (∆ku70FRT2). Illumina sequencing of both RNA libraries produced 84,322,825 mapped reads. To distinguish between Dicer-dependent and independent sRNA formation, we further constructed two single dicer gene mutants (∆dcl2 and ∆dcl1) and a dicer double mutant (∆dcl2∆dcl1) and analyzed an sRNA library from the Dicer-deficient double-mutant. We identified 661 Dicer-dependent loci and in silico prediction revealed 34 milRNAs. Northern blot hybridization of two milRNAs provided evidence for mature milRNAs that are processed either in a complete or partial Dicer-dependent manner from an RNA precursor. Identified milRNAs share typical characteristics of previously discovered fungal milRNAs, like a strong preference for a 5' uracil and the typical length distribution. The detection of potential milRNA target sites in the genome suggests that milRNAs might play a role in posttranscriptional gene regulation. Our data will further increase our knowledge of sRNA dependent gene regulation processes, which is an important prerequisite to develop more effective strategies for improving industrial fermentations with P. chrysogenum.